Text and context : an examination of the way in which John's prologue has been interpreted by selected writers : Origen, Luther and Bultmann - Latham, Jonathan Cyril (Rhodes University, Faculty of Divinity, Department of Divinity, 1988)
In chapter one of this work, as a preliminary to the formulation of the question that this thesis will attempt to answer, the changing understanding of the part played by the interpreter in the process of interpretation is discussed. This outline begins with the understanding of the role of the interpreter in liberal theology - where he is thought of as one who applies critical methods to the text in a detached and scientific way. After this the hermeneutic spiral is discussed - the formation of this model acknowledges to a greater degree the individual and human part played by the interpreter. This is followed by a brief examination of the most recent theories of interpretation in which meaning is regarded as residing not in the text but in the interpreter himself. The task of this thesis is to determine whether, as these recent theorists suggest, the reader creates meaning instead of reading out what somehow lies in the text itself. The task of this thesis is to ascertain, by studying the interpretationsof John's Prologue by Origen, Luther and Bultmann, whether the text does in fact operate as a series of sign-posts that pOint the interpreter to a destination within his own semantic universe. This may be determined by noting whether or not the contexts, i n the broadest sense, of these interpreters have played a formative part in their interpretations. contextual influences are regarded as existing wherever there is a procedure or meaning in the interpreter's commentary which one expe cts to find there as a result of one's knowledge of the interpreter's life and previous writings. Our research reveals that Orige n, Luther and Bultmann have produced three very different commentaries in which the common denominator is the formative influence of the interpreter's context. Each of these writers has produced an interpretation that is consistent, in both approach and theology, with their previous exegetical and theological thought. This indicates that contextual factors have played a significant part in determining their interpr etations of John 1 :1-18. It would appear that these interpreters have been led to find the meaning of John's Prologue not with reference to any new, unprecedented set of symbols, but with reference to their own, well-worn semantic universes. In the conclusion it is noted that this research appears to support what many modern theorists have said as to the locus of meaning in interpretation. In the conclusion it is also noted that many of the fears raised by these findings - that readers and writers, or speakers and hearers, may become so isolated and trapped in their own thought worlds that any real contact with the outside is impossible - may be groundless. These findings also point to a certain consistency between the interpreters and their communities. This refutes the fears as to the isolation and solitary development of the individual in that it points to a certain community or corporate aspect which plays a part in the development of the indivi dual's semantic universe .,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Bible -- John -- Criticism, interpretation etc.